If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10z + -9z + -3 = 1 Reorder the terms: -3 + 10z + -9z = 1 Combine like terms: 10z + -9z = 1z -3 + 1z = 1 Solving -3 + 1z = 1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1z = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 1z = 1 + 3 1z = 1 + 3 Combine like terms: 1 + 3 = 4 1z = 4 Divide each side by '1'. z = 4 Simplifying z = 4
| 4/3÷1/2 | | (3x+5)=2 | | Y=4(-1X^2)-1 | | -3c-7c=18 | | 3(2x-4)+2=(2x-1)-3(x-4) | | (x^2+5x+6)(x-1)=(x^2+8x+16)(x-4)+7 | | 4/5=2/.06 | | s=2lh+3lh | | 12/7n-1/21n=n-2/3 | | 16x^2-362=0 | | 3r+7r= | | 0.2b+8=0.5b+15 | | 7(d-7)+2=9 | | 8x+5=86 | | 3/64n=-13/4n-18 | | 2.5x+2.5y=17 | | 3d+8b=-23 | | -x+3=37 | | x^2-x=26 | | p+y=152 | | x/9-3=12 | | 168/w=7/12 | | 7x-2(x-1)=-3x+7x+7 | | 6.1(3x+7)=134.5 | | 7-3.(-4)-27/(-9) | | 6c+3c=-21 | | -8-22=8*-2 | | -4h+9=41 | | a-8c= | | 2x+5-10x+14=0 | | -7*-2-2*-8=2 | | X^2-4KX+36= |